New Acoustics Based on Metamaterials - Gan, Woon Siong (Engineering Materials,, 2018)
This book highlights the acoustical metamaterials' capability to manipulate the direction of sound propagation in solids which in turn control the scattering, diffraction and refraction, the three basic mechanisms of sound propagation in solids. This gives rise to several novel theories and applications and hence the name new acoustics. As an introduction, the book mentions that symmetry of acoustic fields is the theoretical framework of acoustical metamaterials. This is then followed by describing that acoustical metamaterials began with locally resonant sonic materials which ushered in the concept of negative acoustic parameters such as mass density and bulk modulus. This complies with form invariance of the acoustic equation of motion which again exemplifies the symmetry property of acoustic fields.